Hubungan Antara Kecerdasan Emosi, Adversity Quotient dan Efikasi Diri Pada Siswa Kelas XII Madrasah Aliyah Negeri 1 Magelang - Moersito Wimbo Wibowo (University of Merdeka Malang, 2015)
This study aims to determine the relationship between emotional intelligence, adversity quotient and self-efficacy of class XII students in welcoming UAN (Ujian Akhir Nasional). The research samples count to 122 students. This research used multiple regression analysis techniques. From the correlation analysis it is known that there is a positive correlation between emotional intelligence and self-efficacy in grade XII MAN 1 Magelang (rx1y = 0,6; p = 0,000) which means that the first hypothesis is accepted. Furthermore, there is positive relationship between adversity quotient and self-efficacy in grade XII students MAN 1 Magelang (rx2y = 0,285; p = 0,01) which means that the second hypoyhesis of the study is also accepted. The third hypothesis that there is a positive relationship between emotional intelligence and adversity quotient simultaneously with self-efficacy was accepted because R = 0,61 and F count F table (35,203 3,072).